Optimization of Early Childhood Language Development through Storytelling Methods at KB Pangeran Purbaya Kalisoka Dukuhwaru Tegal - Laeli Nur'Afita, Luthfatul; Fajriyatul Rosyidah, Agustina; Ainatus Syifa, Aski; Harti, Sri; Pertiwi Dwi Widiatin, Nurul; Lanahdiana, Aufa; Fatikhatuz Zahrani, Nadila; Hamid Samiaji, Mukhamad (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Language development is one of the very important aspects stimulated in early childhood. This study aims to explain the role of storytelling methods on early childhood language development in KB Pangeran Purbaya Kalisoka Dukuhwaru Tegal. This research is included in descriptive-qualitative research with case study methods. The data collection techniques used are observation, interviews and documentation. The results of the study illustrate that storytelling methods can improve language development in early childhood, especially speech skills. The increase was obtained because of the presentation of the storytelling method using colorful book media so that it is fun and fun and trains speech skills with the courage to appear to tell stories in front of the class. The storytelling method is also interesting because it uses hand puppet media, power point media and audiovisual media. The storytelling method can also improve children's listening skills and vocabulary skills by using various themes, simple sentences and easy for children to understand. The implications of applying the storytelling method play a role in early childhood language development, help the learning process so that learning objectives can be achieved properly, and create a joyful atmosphere and not quickly boring for children when learning.